Pelatihan Desain Pembelajaran STEM-ESD untuk Guru SMA Wujudkan Hidup Berkelanjutan - Purwianingsih, Widi Purwianingsih; Ari Widodo; Riandi; Siti Sriyati; Rini Solihat (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: The purpose of this community service is to design STEM-ESD-based learning for high school teachers to foster a sustainable lifestyle for students. Research methodology: The training used the lesson study (plan-do-see) activity pattern. This community service was carried out for teachers in Tasikmalaya City and Regency with approximately 30 participants through four meetings. Results: The results showed that teachers can determine materials, identify problems, and create teaching modules. In the open lesson activity, the implementation of learning was carried out optimally, and all students were monitored actively and participated in the activities well. The participant responses were also good. Conclusions: Most teachers were able to create content representations (COREs) for concepts that would be used in the teaching module. Teachers also felt that the training had succeeded in broadening their horizons and providing useful knowledge related to STEM-ESD-based teaching. Limitations: The training period was limited, potentially limiting the ability to comprehensively capture long-term changes. The training participants faced challenges in selecting the right materials to be taught through the STEM-ESD approach as well as in identifying and formulating the problems that needed to be solved. Nevertheless, participants' responses to the training were positive. Contribution: This training provides new knowledge to high school teachers that STEM-ESD-based learning can train students to think critically and creatively, solve problems using technology, and foster a sustainable lifestyle for students.